2012
DOI: 10.1597/10-156
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction after Prosthetic Rehabilitation of Bone-Grafted Alveolar Clefts with Nonsubmerged ITI Straumann Dental Implants Loaded at Three Months

Abstract: Implant-borne prosthetic rehabilitation of bone-grafted clefts with nonsubmerged ITI Straumann implants with 3 months' loading represents a reliable treatment option with high success rates in the long term. Functional aspects are comparable to those of noncleft patients. The oral-health-related quality of life of cleft patients is similar to that of noncleft patients. Aesthetics are restricted but satisfactory to patients and dental professionals. Aesthetics of peri-implant soft tissues should be improved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
18
0
4
Order By: Relevance
“…OHIP-14 has previously been translated into Norwegian and used in a large study (n = 3538) with a calculated Norwegian national norm value [32]. Although previous studies have reported PROMs in relation to bone grafting [9,[33][34][35][36][37][38][39][40][41][42], to our knowledge, only one previous study has systematically assessed impact of donor site harvesting on OHRQoL, where (a) a postoperative lowering of OHRQoL was observed following bone grafting from both intra-oral and extra-oral sites and (b) iliac crest grafts compared to intraoral donor sites had a negative impact on postoperative QoL [37]. Moreover, to our knowledge, only one study has previously assessed the cost-effectiveness of autologous iliac crest grafting [43].…”
Section: Introductionmentioning
confidence: 99%
“…OHIP-14 has previously been translated into Norwegian and used in a large study (n = 3538) with a calculated Norwegian national norm value [32]. Although previous studies have reported PROMs in relation to bone grafting [9,[33][34][35][36][37][38][39][40][41][42], to our knowledge, only one previous study has systematically assessed impact of donor site harvesting on OHRQoL, where (a) a postoperative lowering of OHRQoL was observed following bone grafting from both intra-oral and extra-oral sites and (b) iliac crest grafts compared to intraoral donor sites had a negative impact on postoperative QoL [37]. Moreover, to our knowledge, only one study has previously assessed the cost-effectiveness of autologous iliac crest grafting [43].…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few articles in the literature focused on implantological treatment of the cleft. Landes et al [23] demonstrated in a study that the probability of success of implants in patients with cleft is very similar to prognosis of implants inserted after traumatic tooth loss. The oral-health-related quality of life of cleft patients is similar to that of noncleft patients.…”
Section: Discussionmentioning
confidence: 98%
“…Landes et al 4 citaram que o implante em área de fissura é uma opção de tratamento confiável, com elevadas taxas de sucesso em longo prazo. Os aspectos funcionais são comparáveis aos de pacientes não-fissurados.…”
Section: Discussionunclassified
“…As opções de tratamento incluem o fechamento ortodôntico do espaço edêntulo, a adaptação de pontes fixas convencionais ou a inserção de um implante dentário, relatado, pela primeira vez, há quase 30 anos, por Verdi et al 3 Devido a vantagens, como a conservação dos dentes adjacentes e o resultado estético mais favorável, a inserção de implantes em pacientes com fissura labiopalatina tornou-se um tratamento considerável, alcançando resultados com uma enorme satisfação funcional e, além disso, o osso enxertado na fenda é protegido dos processos de reabsorção quando sofre carga funcional por um implante dentário 2,4 .…”
Section: /204unclassified